Revisiting Vitruvius’ Town Planning Method in Architectural Education - Andri Yatmo, Yandi; Atmodiwirjo, Paramita (Nakhara : Journal of Environmental Design and Planning, 2023)
This paper discusses the method of town planning described in Vitruvius’ Ten Books on Architecture and explores the possibility of its application in the process of design learning in architectural education. In particular, it addresses the prescriptive nature of the texts that outlined the method of town planning as an example of contextual strategies to highlight the key aspects of the design methodology to be followed in a structured manner. To explore the extent to which this method is applicable in a real design process, Vitruvius’ texts on town planning became the basis for method exploration in a class of undergraduate architectural education. The exercise of developing a set of town plans following the principles highlighted in the texts demonstrates the robustness of the methods outlined by Vitruvius. Revisiting Vitruvius’ methods through this exercise becomes a way to understand and rethink the position of Vitruvius’ texts within current architectural practice and education.